СОЦИАЛЬНО-ПСИХОЛОГИЧЕСКИЕ ОСОБЕННОСТИ И ДИНАМИКА УДОВЛЕТВОРЁННОСТИ БРАКОМ У МУЖЧИН И ЖЕНЩИН В КАРАКАЛПАКСКОЙ СЕМЬЕ - Утепбергенов, М.А. (SCIENCE and SOCIETY, 2019)
The author of the article researches the degree of satisfaction by marriage in the rural and urban families. The author points out that the satisfaction by marriage in the cities and villages are different. The degree of satisfaction by marriage in the villages is higher than in the cities. It is connected with the typical peculiarity, as the rural family is definitely a keeper of the “past”, where the leading factors of steadiness of the marriage are traditional, social, economical factors, relative relationship, stable traditions of family relationships.
Keywords: ethno psychological peculiarities; the degree of satisfaction by marriage; firmness of marriage; dynamics of feelings; urban family; rural family